Cystathionine β‐synthase regulates mitochondrial morphogenesis in ovarian cancer. Issue 8 (1st March 2018) - Kumar Chakraborty, Prabir; Murphy, Brennah; Banerjee Mustafi, Soumyajit; Dey, Anindya; Xiong, Xunhao; Rao, Geeta; Naz, Sarwat; Zhang, Min; Yang, Da; Dhanasekaran, Danny N.; Bhattacharya, Resham; Mukherjee, Priyabrata
Abstract : Deregulation of mitochondrial morphogenesis, a dynamic equilibrium between mitochondrial fusion and fission processes, is now evolving as a key metabolic event that fuels tumor growth and therapy resistance. However, fundamental knowledge underpinning how cancer cells reprogram mitochondrial morphogenesis remains incomplete. Here, we report that cystathionine β‐synthase (CBS) reprograms mitochondrial morphogenesis in ovarian cancer (OvCa) cells by selectively regulating the stability of mitofusin 2 (MFN2). Clinically, high expression of both CBS and MFN2 implicates poor overall survival of OvCa patients, and a significant association between CBS and MFN2 expression exists in individual patients in the same data set. The silencing of CBS by small interfering RNA or inhibition of its catalytic activity by a small molecule inhibitor creates oxidative stress that activates JNK. Activated JNK phosphorylates MFN2 to recruit homologous to the E6‐AP carboxyl terminus' domain‐containing ubiquitin E3 ligase for its degradation via the ubiquitin‐proteasome system. Supplementation with hydrogen sulfide or glutathione (the catalytic products of CBS enzymatic activity), anti‐oxidants, or a JNK inhibitor restores MFN2 expression. In CBS‐silenced orthotopic xenograft tumor tissues, MFN2 but not MFN1 is selectively downregulated. In summary, this report reveals a role for deregulated mitochondrial morphogenesis in OvCa, suggests one of the mechanisms for this deregulation, and provides a way to correct it through modulation of the metabolic enzyme CBS.—Chakraborty, P. K., Murphy, B., Mustafi, S. B., Dey, A., Xiong, X., Rao, G., Naz, S., Zhang, M., Yang, D., Dhanasekaran, D. N., Bhattacharya, R., Mukherjee P. Cystathionine b‐synthase regulates mito‐chondrial morphogenesis in ovarian cancer. FASEB J . 32, 4145–4157 (2018). www.fasebj.org